Compliance therapy: a randomised controlled trial in schizophrenia. Issue 7419 (9th October 2003) - O'Donnell, Colin; Donohoe, Gary; Sharkey, Louise; Owens, Nicholas; Migone, Maria; Harries, Raewynn; Kinsella, Anthony; Larkin, Conall; O'Callaghan, Eadbhard
Abstract: >Objective To evaluate the efficacy of "compliance therapy" for improving adherence to prescribed drug treatment among patients with schizophrenia. Design Randomised controlled trial. Setting Urban catchment area psychiatric service. Participants 94 consecutive admissions of patients with schizophrenia, 56 agreed to participate. Intervention Compliance therapy and non-specific counselling, each consisting of 5 sessions lasting 30-60 minutes. Main outcome measures Compliance with drug treatment at one year; attitudes to treatment, symptomatology, insight, and quality of life at one year; length of "survival" in the community, bed days, and rehospitalisation rates at two years. Results Compliance therapy did not confer a major advantage over non-specific therapy in improving compliance at one year (43% (12/28) v 54% (15/28), difference −11% (95% confidence interval −37% to 15%) or in any of the secondary outcome measures—symptomatology, attitudes to treatment, insight, global assessment of functioning, and quality of life. Conclusion Compliance therapy may not be of benefit to patients with schizophrenia. Attitudes to treatment at baseline predicted adherence one year later and may be a clinically useful tool.